PRELIMINARY RESEARCH ON DANAUS CHRYSIPPUS L. (LEPIDOPTERA: DANAIDAE) IN DALAT - Nguyễn Thanh Thủy Tiên (Tạp chí Khoa học Đại học Đà Lạt)
Danaus chrysippus L. (Lepidoptera: Danaidae) is one of the beautiful butterflies which is usually displayed in insect collections for researching, studying and commercial purposes. This study focuses on collecting data on the morphological and biological characteristics of the Danaus chrysippus L. in Dalat.In the research, eggs, larvae, and pupae of this butterfly were collected from plants of Asclepias in the nature and were developed later in insect cages under laboratory conditions. The larvae were fed on Gomphocarpus fruticosus leaves and the adults were fed on sugar solution 10%. The results showed that the development time of Danaus chrysippus L. on average from egg to adult is 40,79 days. The longevity was 26,25±5,57 days and the fecundity was 35,33±7,02 eggs, on average. These results will provide basic data for the rearing process of this butterfly in Dalat in the future.